2016
DOI: 10.15562/jdmfs.v1i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Differences chronological age and dental age using Demirjian method based upon a study radiology using radiography panoramic at the Dental Hospital Hasanuddin University

Abstract: Background.Choronological age is assessed by the date, month, and year of birth. Several researches suggested that Chronological age may not be able to provide sufficient information regarding on human growth precisely. Chronological age, on the other hand, could not be used to assess  Maturity development rate of a patient, so it is necessary to assess the dental age. Dental age is age assessment method  by measuring human growth and development. Age estimation has important role in health field, Particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a French study, Demirjian’s method was found to overestimate age by 1.17 years when applied to children aged 6.0–11.5 years old [ 39 ]. In addition, Yunus and Wardhani examined 30 panoramic radiograph samples of Indonesian children aged 4–9 years old using the Demirjian method [ 40 ]. The results showed low accuracy because of significant overestimation of dental age compared with the chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…In a French study, Demirjian’s method was found to overestimate age by 1.17 years when applied to children aged 6.0–11.5 years old [ 39 ]. In addition, Yunus and Wardhani examined 30 panoramic radiograph samples of Indonesian children aged 4–9 years old using the Demirjian method [ 40 ]. The results showed low accuracy because of significant overestimation of dental age compared with the chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…(Veera et al, 2014) Previous studies reported the assessment of chronological and dental age based on panoramic radiography. (Godge et al, 2014;Yunus and Wardhani, 2016) Meanwhile, the estimation of dental age can identiied using CPCI method, which is calculated through the correlation between the reduction of the coronal pulp cavity and the chronologicalage.Lower premolars and molars wereconsidered in this method, as the mandibular teeth are more visiblethan the maxillary ones. (Priyadarshini et al, 2015;Putri et al, 2013) The youngest sample of this study aged 21 years and the oldest age of the group is 30 years with the proportion of male and female is the same 50% (n = 30) as described in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Yunus and Wardhani in 2016, 30 panoramic radiograph samples of Indonesian children between 4–9 years old were calculated using the Demirjian method. The result showed that the Demirjian method is less accurate because there is a significant overestimation of dental age compared with the chronological age [ 22 ].…”
Section: Tooth Growth and Developmentmentioning
confidence: 99%